Effect of dietary supplements on athletic performance in elite soccer players: a systematic review - Abreu, R (2022)
Review question / Objective: The aim of this systematic review is to evaluate the effect of dietary supplements on athletic performance in elite soccer players. Eligibility criteria: This review will be conducted based on the PRISMA guidelines and the PICOS approach. Articles were eligible if they were published or in-press in peer-reviewed journals (i.e., abstracts published in conference proceedings, books, theses, and dissertations will not be considered), published in English language with available abstract for screening. The PICOS approach will be established as follows: Population: highly trained or elite, adult (>18 years old) male or female soccer players; Intervention: use of one or more dietary supplements for performance; Comparison: same conditions with placebo or without dietary supplements; Outcome: athletic or soccer-related performance outcomes; Study design: intervention in parallel groups or with crossover, blind or double-blind, and randomized controlled trials (experimental studies).